2020
DOI: 10.4103/jfmpc.jfmpc_340_20
|View full text |Cite
|
Sign up to set email alerts
|

Asthenopia among university students: The eye of the digital generation

Abstract: Background: Asthenopia or eye strain is one of the major medical problems that students face during their academic years. Objectives: The aim of this study is to determine the prevalence of asthenopia among a sample of university students attending various majors and to identify the risk factors for its development. Methods: This is a cross sectional study conducted on students attending various faculties at the American University of Beirut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
2
12
0
11
Order By: Relevance
“…This is in line with the ndings of several studies conducted in Middle Eastern and Asian countries. 14,15,21 Contrary to the hypothesis, manual workers developed new symptoms of DES more than other occupations (OR 1.42, 95 % C.I). The reason for this is that manual workers used digital devices for communication and online services more than they did previously.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This is in line with the ndings of several studies conducted in Middle Eastern and Asian countries. 14,15,21 Contrary to the hypothesis, manual workers developed new symptoms of DES more than other occupations (OR 1.42, 95 % C.I). The reason for this is that manual workers used digital devices for communication and online services more than they did previously.…”
Section: Discussionmentioning
confidence: 62%
“…Research studies provide similar ndings, but the symptoms occur in a different order that is re ective of sampling and geographical variations. 15,21,30,31 Dry eye symptoms might not be a legitimate component of DES, as dry eye disease may aggravate accommodative symptoms, especially in elderly men and women, as well as those who have ocular surface disease. However, DES affects people under the age of 18 who use digital devices; this necessitates the need to develop a more speci c and precise de nition of DES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In present study, age-group > 18 years were included which presents more appropriate statistical representation of population, as in today' era, all age-group people are using digital devices more frequently. In similar study conducted by Touma S. et al 9 at Beirut, Lebanon, the gender distribution was 55.4% males and 44.6% were females while Khan A. et al 7 in their study at Mangluru, Karnataka, India reported almost equal proportion of gender distribution.…”
Section: Discussionmentioning
confidence: 76%
“…Dessie et al 12 in their study found Calculated Odds' ratio significant for number of working hours (>4.6) on computer/day while Reddy SC et al 11 in Nepal found duration of Computer use (> 2 hours/day) and wearing spectacles had statistically significant association with DES. Sawaya et al 9 in their study at Lebanon found significant adjusted Odds' ratio for participants using both glasses and contact lens. AI Tawil et al 10 reported regarding computer vision syndrome prevention, factors such as hours of use, screen distance, screen brightness, and room illumination showed statistically significant difference similar findings were reported in present study in terms of statistical significant association between presence of risk factors like higher average time spent for digital device usage per day, lesser approximate distance of digital device from eyes and not taking preferred break after 30 minutes and occurrence of symptoms of DES (Table 3).…”
Section: Discussionmentioning
confidence: 90%